2020
DOI: 10.1101/2020.05.15.096628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interpretable deep learning of label-free live cell images uncovers functional hallmarks of highly-metastatic melanoma

Abstract: Deep convolutional neural networks have emerged as a powerful technique to identify hidden patterns in complex cell imaging data. However, these machine learning techniques are often criticized as uninterpretable "black-boxes" -lacking the ability to provide meaningful explanations for the cell properties that drive the machine's prediction. Here, we demonstrate that the latent features extracted from label-free live cell images by an adversarial auto-encoding deep convolutional neural network capture subtle d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 93 publications
(112 reference statements)
1
30
0
Order By: Relevance
“…Meanwhile, it has been shown that DL techniques can holistically capture complex structural features for classification. This has found broad applications in detecting cell types (12)(13)(14), cell states (15)(16)(17)(18)22), drug response (19), and stem cell lineage (20). By fully leveraging the label-free and high multiplexing nature of our technique, it can potentially generate significant impacts in imaging cytometry by offering unprecedented information content and discovering new compound morphological features necessitating multiplexed fluorescence readout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, it has been shown that DL techniques can holistically capture complex structural features for classification. This has found broad applications in detecting cell types (12)(13)(14), cell states (15)(16)(17)(18)22), drug response (19), and stem cell lineage (20). By fully leveraging the label-free and high multiplexing nature of our technique, it can potentially generate significant impacts in imaging cytometry by offering unprecedented information content and discovering new compound morphological features necessitating multiplexed fluorescence readout.…”
Section: Discussionmentioning
confidence: 99%
“…By doing so, multiple subcellular structures and cell states can be revealed simultaneously without physical labeling. While previous work has shown that DL models can disentangle the complex structures captured in the label-free data and make in-silico fluorescence labeling with high accuracy (10)(11)(12) or holistically capture "hidden" structural features that are not easily perceived or described (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), these results are fundamentally limited by the weak structural contrast from the transmission modes that contain only forward scattering information. By exploiting the enhanced resolution and sensitivity in the backscattering data, we demonstrate a dramatic increase in the fluorescence prediction accuracy with up to 3× improvement as compared to the current state-of-the-art.…”
Section: Introductionmentioning
confidence: 99%
“…We used self-supervised deep learning ( Figure 1E) to build an unbiased model of microglia morphology. Recent work has demonstrated that self-supervised learning with autoencoders (5,6) can provide a quantitative model of cell morphology informed by all of data.…”
Section: Learning a Latent Representation Of Morphology Thatmentioning
confidence: 99%
“…Recent work on analysis of morphological states of cells has relied on images of fixed cells labeled with a panel of fluorescent markers (1), live three-dimensional imaging of the membrane labeled with genetic markers (2), and phase contrast imaging of live cells (3)(4)(5)(6). The morphological states have been analyzed with low dimensional representations computed with geometric or biophysical models (3,(7)(8)(9)(10)(11), supervised learning of morphological labels (4,(12)(13)(14)(15)(16)(17), and, recently, self-supervised learning of latent representations of morphology (5,6). These analytical approaches have been inspired by the need for quantitative descriptions of specific, complex biological functions, such as motility of single cells (2,3,7,8,18), collective cell migration (9,11), cell cycle (4,12,13), spatial gene expression (17), and spatial protein expression (14,16).In addition, data-driven integration of the morphology and gene expression (13,17,(19)(20)(21)(22) is now enabling rapid analysis of functional roles of genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation